Formulation Of Topical Self-Nanoemulsifying Drug Delivery Systems (SNEDDS) Of Vitamin D3 - Adeltrudis Adelsa Danimayostu; Ronny Martien; Endang Lukitaningsih; Retno Danarti (Poltekkes Kemenkes Surakarta, 2022)
Background: In the last few decades, there has been a significant increase in customers’ interest in skin care, including anti-aging. One of the skin care substances, vitamin D3, has a positive impact on the skin, such as the keratinocyte differentiation effect to maintain the skin barrier and the hydration effect to keep the skin moist. Vitamin D3 has a high lipophilicity, so it is considered ideal to formulate in the self-nano emulsifying drug delivery system (SNEDDS). The higher solubility of vitamin D3 in the SNEDDS oil component could improve its penetration through the skin. The SNEDDS is a primary dosage form that can be entrapped in semisolid base dosage forms, such as cream, lotion, or gel. SNEDDS vitamin D3 needs to be optimized to obtain the appropriate composition of the components: oil, surfactant, and co-surfactant. Methods: The D-Optimal Mixture method using Design Expert 10 software had been chosen as an optimization tool for SNEDDS vitamin D3. Results: The composition of the optimum formula was obtained as follows: 1.0351 g Miglyol 812 N; 3.0637 g Tween 80 and 0.9011 g PEG 400. The optimum formula has a particle size of 32.62 nm ± 1.80 nm and a polydispersity index of 0.31 ± 0.03. Conclusion: The release test was carried out with the help of a Franz diffusion cell instrument, a cellophane membrane, and phosphate-buffered saline pH 7.4 containing 0.5% Tween 80. The cumulative amount of vitamin D3 released per minute (Flux) was 0.10 µg/min.